On-sun operation of a 150 kWth pilot solar receiver using dense particle suspension as heat transfer fluid. (1st November 2016) - Perez Lopez, I.; Benoit, H.; Gauthier, D.; Sans, J.L.; Guillot, E.; Mazza, G.; Flamant, G.
Graphical abstract: Highlights: Pilot scale 16-tube cavity solar receiver operated with fluidized particles as HTF. The pilot solar receiver power reached up to 150 kW. Particles circulated in closed loop during hours in the complete solar ring. Particle mass flow rate variation in the range 660–1760 kg/h was performed. Solar receiver efficiency up to 90% was achieved ( Gp = 44 kg/m 2 .s; Tp, o = 370 °C). Abstract: Previous studies proved the Dense Particle Suspension (DPS) - also called Upward Bubbling Fluidized Bed (UBFB) - could be used as Heat Transfer Fluid (HTF) in a single-tube solar receiver. This article describes the experiments conducted on a 16-tube, 150 kWth solar receiver using a dense gas-particle suspension (around 30% solid volume fraction) flowing upward as HTF. The receiver was part of a whole pilot setup that allowed the continuous closed-loop circulation of the SiC particles used as HTF. One hundred hours of on-sun tests were performed at the CNRS 1 MW solar furnace in Odeillo. The pilot was tested under various ranges of operating parameters: solid mass flow rate (660–1760 kg/h), input solar power (60–142 kW), and particle temperature before entering the solar receiver (40–180 °C). Steady states were reached during the experiments, with continuous circulation and constant particle temperatures. For the hottest case, the mean particle temperature reached 430 °C in the collector fluidized bed, at the receiver outlet, and it went up to 700 °C at the outlet of the hottest tube, during steady operation. A temperature difference between tubes is observed that is mainly due to the incident solar flux distribution heterogeneity. The thermal efficiency of the receiver, defined as the ratio of power transmitted to the DPS in the form of heat over solar power entering the receiver cavity, was calculated in the range 50–90% for all the experimental cases. The system transient responses to variations of the solar irradiation and of the solid mass flow rate are also reported.